Price Discount, Ease of Payment, and Self Control Effect Analysis on Impulse Buying in ShopeFood Application - Shinta Kamilia Sari; Mutya Azzahra; Agustina Agustina (Cita Konsultindo Research Center, 2024)
The purpose of this study was to test Impulse Buying, Price Discount, Ease of Payment and Self Control. This study focuses on Shopeefood Marketplace consumers using a saturated sample of 150 people with non-probability sampling techniques. The questionnaire was disseminated through social media. The data collection method uses observation, questionnaires and literature studies. The data processing technique in this study uses the help of a Structural Equation Model (SEM) based on Partial Least Square (PLS) 3.0. The results of the analysis in this study indicate that price discounts, ease of payment, and self-control have a positive and significant effect on impulse buying in ShopeeFood service users.